Characterization of chromosome composition of sugarcane in nobilization by using genomic in situ hybridization - Fan Yu; Ping Wang; Xueting Li; Yongji Huang; Qinnan Wang; Ling Luo; Yanfen Jing; Xinlong Liu; Zuhu Deng; Jiayun Wu; Yongqing Yang; Rukai Chen; et al. (Molecular Cytogenetics, 2018)
Abstract Background Interspecific hybridization is an effective strategy for germplasm innovation in sugarcane. Nobilization refers to the breeding theory of development and utilization of wild germplasm. Saccharum spontaneum is the main donor of resistance and adaptive genes in the nobilization breeding process. Chromosome transfer in sugarcane is complicated; thus, research of different inheritance patterns can provide guidance for optimal sugarcane breeding. Results Through chromosome counting and genomic in situ hybridization, we found that six clones with 80 chromosomes were typical S. officinarum and four other clones with more than 80 chromosomes were interspecific hybrids between S. officinarum and S. spontaneum. These data support the classical view that S. officinarum is characterized by 2n = 80. In addition, genomic in situ hybridization showed that five F1 clones were products of a 2n + n transmission and one F1 clone was the product of an n + n transmission in clear pedigree noble hybrids between S. officinarum and S. spontaneum. Interestingly, Yacheng 75–408 and Yacheng 75–409 were the sibling lines of the F1 progeny from the same parents but with different genetic transmissions. Conclusions This is the first clear evidence of Loethers, Crystallina, Luohanzhe, Vietnam Niuzhe, and Nanjian Guozhe were typical S. officinarum by GISH. Furthermore, for the first time, we identified the chromosome transmission of six F1 hybrids between S. officinarum and S. spontaneum. These findings may provide a theoretical basis for germplasm innovation in sugarcane breeding and guidance for further sugarcane nobilization.